How autophagy, a potential therapeutic target, regulates intestinal inflammation - Chen, Shuang-Lan; Li, Chun-Meng; Li, Wei; Liu, Qing-Song; Hu, Shuang-Yuan; Zhao, Mao-Yuan; Hu, Dong-Sen; Hao, Yan-Wei; Zeng, Jin-Hao; Zhang, Yi (Frontiers in Immunology, 2023)
Autophagy is a catabolic mechanism that protects cells after a cellular stress response by removing damaged organelles and proteins from the cell. The link between autophagy-related genes and intestinal health has been extensively studied, and the role of autophagy on intestinal inflammation through cellular pathways, endoplasmic reticulum stress (ERS), and microflora, but the role of autophagy on inflammatory bowel disease(IBD) is also cell-specific and context-specific. Here, we review the role of autophagy in IBD and how it exacerbates intestinal inflammation, which may inform future research on the pathogenesis of IBD and disease management.